Anodic stripping voltammetry at bismuth-modified electrodes in ammonia-buffered media - Švancara, Ivan (Univerzita Pardubice, 2007)
In this contribution, the analytical performance of a bismuth-modified carbon paste electrode (Bi-CPE) in square-wave anodic stripping voltammetry (SWASV) with ammonis buffer-based supporting media (pH 8.6-9.0) has been studied. Possibilities and limitations of such combination used fir the determination of various metal ions were explored with tje electrode of choice, containing 17 % (w/w) Bi, when analysing model solutions with Mn2+, Zn2+, Cd2+, Pb2+, In3+, and Tl+ - added in as either single species or selected mixtures. SWASV of these ions has been investigated focused on the individual peak characteristics, calibration measurements and definition of linear concentration ranges attainable, limits of detections, reproducibility, and interference effects from other ions. The latter was examined in more detail for Zn2+ + Cd2+ + Pb2+ and, particularly, for Tl+ + Cd2+ + Pb2+ mixtures where the formation of intermetallic compounds and low-melting alloys with bismuth had significantly affected the SWASY detection of the respective metals, giving rise to overlapped and additional signals. As shown, these phenomena would represent one of the key-factors which have to be considered when elaborating procedures for practical determinations.
Keywords: anodická rozpouštěcí voltametrie; Bismutové elektrody; stanovení kovů